Cohort study evaluating the burden of wounds to the UK's National Health Service in 2017/2018: update from 2012/2013. Issue 12 (22nd December 2020) - Guest, Julian F; Fuller, Graham W; Vowden, Peter
Abstract : Objective: To evaluate the prevalence of wounds managed by the UK's National Health Service (NHS) in 2017/2018 and associated health outcomes, resource use and costs. Design: Retrospective cohort analysis of the electronic records of patients from The Health Improvement Network (THIN) database. Setting: Primary and secondary care sectors in the UK. Participants: Randomly selected cohort of 3000 patients from the THIN database who had a wound in 2017/2018. Primary and secondary outcome measures: Patients' characteristics, wound-related health outcomes, healthcare resource use and total NHS cost of patient management. Results: There were an estimated 3.8 million patients with a wound managed by the NHS in 2017/2018, of which 70% healed in the study year; 89% and 49% of acute and chronic wounds healed, respectively. An estimated 59% of chronic wounds healed if there was no evidence of infection compared with 45% if there was a definite or suspected infection. Healing rate of acute wounds was unaffected by the presence of infection. Smoking status appeared to only affect the healing rate of chronic wounds. Annual levels of resource use attributable to wound management included 54.4 million district/community nurse visits, 53.6 million healthcare assistant visits and 28.1 million practice nurse visits. The annual NHS cost of wound management was £8.3 billion, of which £2.7 billion and £5.6 billion were associated with managing healed and unhealed wounds, respectively. Eighty-one per cent of the total annual NHS cost was incurred in the community. Conclusion: The annual prevalence of wounds increased by 71% between 2012/2013 and 2017/2018. There was a substantial increase in resource use over this period and patient management cost increased by 48% in real terms. There needs to be a structural change within the NHS in order to manage the increasing demand for wound care and improve patient outcomes.